Clinical Characteristics and Treatment Outcomes for Patients With External Auditory Canal Cholesteatoma. Issue 2 (February 2018) - Morita, Shinya; Nakamaru, Yuji; Fukuda, Atsushi; Fujiwara, Keishi; Hoshino, Kimiko; Homma, Akihiro
Abstract : Objective: We aimed to evaluate the clinical features and treatment outcomes for patients with idiopathic and secondary external auditory canal cholesteatoma (EACC), and to validate the treatment strategy from the perspective of hearing as well as etiology and staging. Study Design: Retrospective case series. Setting: Tertiary referral center and affiliated hospitals. Patients: Fifty-eight patients with idiopathic EACC and 14 patients with secondary EACC. Intervention: Conservative management and surgery. Main Outcome Measure: Air conduction (AC) pure-tone averages (PTAs) and mean air-bone gaps (ABGs). Results: There were no significant differences between hearing values before and after conservative management for idiopathic EACC patients with stages I–III, indicating that hearing abilities were preserved. For idiopathic EACC patients with stage IV disease treated with surgery, the AC PTA threshold and mean ABG significantly improved from a preoperative value of 60.3 dB HL to a postoperative value of 32.4 dB HL ( p  = 0.013), and from 34.3 to 9.5 dB HL ( p  < 0.001), respectively. For secondary EACC, the AC PTA threshold and mean ABG significantly improved from a preoperative value of 49.5 dB HL to a postoperative value of 23.2 dB HL ( p  < 0.001), and from 31.4 to 6.7 dB HL ( p  < 0.001), respectively. Conclusion: The treatment modalities should be selected based on the perspective of hearing as well as the extent of disease and etiology. The early lesions can be treated conservatively, whereas the advanced lesions or cases refractory to conservative management require complete surgical removal of EACC.